Analysis of Islamic Inheritance Law on the Distribution of Women’s Inheritance - Rambe, Dewiyanti; Adly, Muhammad Amar; Khalid, Khalid (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to determine the implementation of the division of women’s inheritance in the Pangkatan sub-district, Labuhan Batu Regency and to find out the perspective of Islamic inheritance law on the distribution of women’s inheritance in the Pangkat Sub-District, Labuhanbatu Regency. Qualitative research methods using observation, interviews, and document studies. The technique of checking the validity of the data used is the degree of trust, transferability, dependability, and certainty. The findings in the study are the implementation of inheritance distribution in the Pangkatan sub-district, which is in accordance with hereditary provisions where sons get 70% inheritance and girls get 30% inheritance, this is because male children are considered to continue their descent. The perspective of Islamic inheritance law in the distribution of inheritance in rank sub-districts is in accordance with faraidh law in addition to the principle of legal clarity and expediency, inheritance law in general and as a whole has positive values, norms, and wisdom which are very basic and contain justice. So, the reform in this research is Islamic Inheritance Law Concerning the Distribution of Women's Inheritance in Rank District Islamic inheritance law, especially the term faraidh and inheritance law in general and as a whole, has very basic positive values, norms, and wisdom and contains very clear positive wisdom reasonableness, in addition to the principle of legal certainty and benefit. The Pangkatan Regency inheritance system which prioritizes the portion of male power holders and the obligation to continue heirs in the family, is analogous to Islamic inheritance law which states that men have greater rights than women. Keywords: Inheritance Division, Islamic Inheritance Law, Women This study aims to determine the implementation of the division of women’s inheritance in the Pangkatan sub-district, Labuhan Batu Regency and to find out the perspective of Islamic inheritance law on the distribution of women’s inheritance in the Pangkat Sub-District, Labuhanbatu Regency. Qualitative research methods using observation, interviews, and document studies. The technique of checking the validity of the data used is the degree of trust, transferability, dependability, and certainty. The findings in the study are the implementation of inheritance distribution in the Pangkatan sub-district, which is in accordance with hereditary provisions where sons get 70% inheritance and girls get 30% inheritance, this is because male children are considered to continue their descent. The perspective of Islamic inheritance law in the distribution of inheritance in rank sub-districts is in accordance with faraidh law in addition to the principle of legal clarity and expediency, inheritance law in general and as a whole has positive values, norms, and wisdom which are very basic and contain justice. So, the reform in this research is Islamic Inheritance Law Concerning the Distribution of Women's Inheritance in Rank District Islamic inheritance law, especially the term faraidh and inheritance law in general and as a whole, has very basic positive values, norms, and wisdom and contains very clear positive wisdom reasonableness, in addition to the principle of legal certainty and benefit. The Pangkatan Regency inheritance system which prioritizes the portion of male power holders and the obligation to continue heirs in the family, is analogous to Islamic inheritance law which states that men have greater rights than women.